Lactobacillus acidipiscis Induced Regulatory Gamma Delta T Cells and Attenuated Experimental Autoimmune Encephalomyelitis - Ren, Saisai; Zhang, Xiaorong; Guan, Hongbing; Wu, Lihong; Yu, Miao; Hou, Dan; Yan, Yongyong; Fang, Xuechun (Frontiers in Immunology, 2021)
Multiple sclerosis is a chronic autoimmune disease involving the central nervous system, and shows a high disability rate. Its pathogenesis is complicated, and there is no good treatment. In recent years, with in-depth studies on the regulation of gastrointestinal flora, the relationship between the mammalian immune system and the intestinal flora has been extensively explored. Changes in the composition and structure of the gastrointestinal flora can affect the characteristics and development of the host immune system and even induce a series of central nervous system inflammation events. The occurrence and development of multiple sclerosis are closely related to the continuous destruction of the intestinal barrier caused by intestinal dysbacteriosis. In this study, we analyzed Lactobacillus acidipiscis in a mouse model of experimental autoimmune encephalomyelitis (EAE). We found that the amount of L. acidipiscis in the intestinal tract was inversely proportional to the progress of EAE development. In addition, the number of CD4+ FOXP3+ regulatory T cells in the mesenteric lymph nodes of mice increased significantly after the mice were fed with L. acidipiscis, and the differentiation of CD4+ T cells to Th1 and Th17 cells was inhibited. However, the protective effect of L. acidipiscis was lost in γδ T cell-deficient mice and hence was concluded to depend on the presence of regulatory γδ T cells in the intestinal epithelium. Moreover, including L. acidipiscis enhanced the development of Vγ1+γδ T cells but suppressed that of Vγ4+γδ T cells. In summary, our results demonstrated the ability of L. acidipiscis to induce generation of regulatory γδ T cells that suppress the development of the encephalomyelitic Th1 and Th17 cells and the progress of EAE.